Theopreneurship dalam Kemandirian Finansial Gereja Perintisan - Franseda Sihite; Henny P Mendrofa (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
Financial independence is very important to ensure the continuation of the ministry of a newly started church. The pastor's family's financial needs and church facilities can be supported by the way the servant of God is an entrepreneur. Theopreneurship contains a theological dimension, namely as a mandate given by God to pastors to manage the potential of themselves and their congregations, even though there are different views about whether a servant of God is an entrepreneur. This study uses the Literature Study method to explain the interests and efforts of a servant of God in entrepreneurship to support the financial independence of the pioneering church. The results of the study found that a servant of God who is starting a new church should be self-employed as a Theopreneur, who acts as a servant (doulus and huperetes) and steward (oikonomos) and also needs to teach, involve and mentor members of the congregation or community whom he serves for joint entrepreneurship so as to effectively achieve the financial independence of the pioneering church for the glory of the Kingdom of God.AbstrakKemandirian finansial sangat penting menjamin kelanjutan pelayanan sebuah gereja yang baru dirintis. Kebutuhan keuangan keluarga gembala dan fasilitas gereja dapat ditopang dengan cara hamba Tuhan itu berwirausaha. Theopreneurship mengandung dimensi teologis yaitu sebagai mandat yang diberikan Tuhan kepada para gembala untuk mengelola potensi diri dan jemaatnya, meski ada perbedaan pandangan soal baik buruknya seorang hamba Tuhan berwirausaha. Penelitian ini menggunakan metode Studi Literatur untuk menjelaskan kepentingan dan upaya seorang hamba Tuhan melakukan wirausaha guna mendukung kemandirian finansial gereja perintisan. Hasil penelitian mendapatkan bahwa seorang hamba Tuhan yang sedang merintis gereja baru patut berwirausaha secara mandiri sebagai seorang Theopreneur, yang berperan sebagai seorang pelayan (doulus dan huperetes)  dan penatalayan (oikonomos),  juga perlu mengajar, melibatkan dan melakukan mentoring terhadap anggota jemaat atau masyarakat yang dilayaninya untuk berwirauaha bersama sehingga efektif mencapai kemandirian finansial gereja perintisan bagi kejayaan Kerajaan Allah.